The Effectiveness of Sim Siaga on The Management of PAIS Teachers at The Office of The Ministry of Religion of Medan City - Ilwan Ilwan; Syafaruddin Syafaruddin; Makmur Syukri (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This paper aims to determine the effectiveness of SIM SIAGA on PAIS teacher management services at the office of the Ministry of Religion (KEMENAG) Medan City. Descriptive qualitative research is used in the article. Data collection was carried out for 3 months, starting from August to October. The technique used in this research is Triangulation (Interview-Documentation-Observation). The results showed that the effectiveness of SIM SIAGA for PAIS teacher services and management at the Ministry of Religion office in Medan City was very satisfying. This can be seen and compared with the EMIS application. Many features help PAIS teachers in bridging the activities and activities carried out. However, this SIM SIAGA application is still in a new category. Therefore, improvements or the best innovations are needed to be able to compete in the future.